Did previous EU-enlargements change the regional distribution of production? An empirical analysis of three enlargement episodes. (30th June 2008) - Huber, Peter
This paper analyses the effects of previous enlargements of the European Union (EU) on the regional structure of production. Focusing on regional development five years before and seven years after integration, we find relatively small and heterogeneous effects. For enlargement by Greece, a robust tendency towards decentralisation is found. For Southern enlargement, effects on border regions are significant for wages and employment, and for Northern enlargement, no significant effects are found. Finally, for nearby old member states, results are contradictory and are not robust to correction for potential bias arising from serial autocorrelation of the error term.